Silicon oxycarbide-antimony nanocomposites for high-performance Li-ion battery anodes. Issue 25 (18th June 2020) - Dubey, Romain J.-C.; Sasikumar, Pradeep Vallachira Warriam; Cerboni, Noemi; Aebli, Marcel; Krumeich, Frank; Blugan, Gurdial; Kravchyk, Kostiantyn V.; Graule, Thomas; Kovalenko, Maksym V.
Abstract : Homogeneously embedded Sb NPs in a SiOC with the size of 5–40 nm were synthesized via the pyrolysis of a preceramic polymer. SiOC/Sb exhibits high rate capability with a charge-storage capacity of 549 mAh g −1 at a current density of 2232 mA g −1 . Abstract : Silicon oxycarbide (SiOC) has recently regained attention in the field of Li-ion batteries, owing to its effectiveness as a host matrix for nanoscale anode materials alloying with Li. The SiOC matrix, itself providing a high Li-ion storage capacity of 600 mA h g −1, assists in buffering volumetric changes upon lithiation and largely suppresses the formation of an unstable solid-electrolyte interface. Herein, we present the synthesis of homogeneously embedded Sb nanoparticles in a SiOC matrix with the size of 5–40 nm via the pyrolysis of a preceramic polymer. The latter is obtained through the Pt-catalyzed gelation reaction of Sb 2-ethylhexanoate and a poly(methylhydrosiloxane)/divinylbenzene mixture. The complete miscibility of these precursors was achieved by the functionalization of poly(methylhydrosiloxane) with apolar divinyl benzene side-chains. We show that anodes composed of SiOC/Sb exhibit a high rate capability, delivering charge storage capacity in the range of 703–549 mA h g −1 at a current density of 74.4–2232 mA g −1 . The impact of Sb on the Si–O–C bonding and on free carbon content of SiOC matrix, along with its concomitant influence on Li-ion storage capacity of SiOC was assessed by Raman and 29 Si and 7 Li solid-state NMR spectroscopies.